2017
DOI: 10.4103/0972-0707.218308
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro study to find the incidence of mesiobuccal 2 canal in permanent maxillary first molars using three different methods

Abstract: Aim:In-vitro study was done to evaluate the incidence of MB2 canals using three different methods (CBCT, CLINICAL ANALYSIS AND DENTAL LOUPES) and to compare the efficacy of the three methods in identifying the incidence of MB2 canals in maxillary permanent first molars.Materials and Methods:The study sample consisted of 120 extracted intact permanent maxillary molars. These extracted teeth were subjected to CBCT. Later the teeth were access opened with naked eye to find the incidence of MB2 canal, and then the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
2
8
1
Order By: Relevance
“…Buhrley et al have found frequencies of MB2 canals in upper 1st molar teeth with the use of magnification were reported to be more as compared to the number found on clinical examination. In vitro studies, conducted to identify the presence of MB2 with and without the use of magnification device, also shown the results in accordance with our study (more number of MB2 are visible under magnification) [20][21][22] . The least percentages were reported by Hassan and Nizar among the Sudanese population 23 .…”
Section: Discussionsupporting
confidence: 91%
“…Buhrley et al have found frequencies of MB2 canals in upper 1st molar teeth with the use of magnification were reported to be more as compared to the number found on clinical examination. In vitro studies, conducted to identify the presence of MB2 with and without the use of magnification device, also shown the results in accordance with our study (more number of MB2 are visible under magnification) [20][21][22] . The least percentages were reported by Hassan and Nizar among the Sudanese population 23 .…”
Section: Discussionsupporting
confidence: 91%
“…1,2,33 MB2 usually has more atresia and its patency cannot be easily achieved compared with the main canal (MB1). 3,5,6 Consequently, overlooking the presence of MB2 is associated with endodontic treatment failure and with the occurrence of periapical lesions. 1,2,3 Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Anatomically, the "critical apical zone" includes the apical third of the root canal, the apical foramen, and its branches (apical foramina or accessory and secondary canal foramina) located within the 3-5 mm root apex. 2,3,5,13 This area is problematic to manage, and available technologies, i.e., cone-beam computed tomography (CBCT) and dental operating microscope (DOM), present limitations and questionable sensitivity in detecting these complexities. 7,15,16 Micro-computed tomography (micro-CT) is considered a superior method for the investigation of root canal anatomy in ex vivo studies, as it provides greater anatomical detail and quantitative data compared to other imaging methods, and avoids the destruction of the specimen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MB2 canals are visualised by histological sections [44], diaphanisation [17], magnifying loupes [41], endodontic surgical microscope [26], scanning electron microscope [44], periapical radiography [40], micro-computed tomographic analysis [27,51], and cone-beam computed tomography (CBCT) [7-9, 57, 58]. However, some of these techniques are invasive, disadvantageous and can only be used to investigate extracted teeth [50]. Nowadays, CBCT has become more widely used because it can provide more reliable diagnostics in the field of endodontics [11,23,34] and can perform morphological analysis of the root canal system [9,30,32,37,58].…”
Section: Introductionmentioning
confidence: 99%